(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In this paper, we will be find numerical solution of Volterra Integral Equation of Second kind through using Implicit trapezoidal and that by using Maple 17 program, then we found that numerical solution was highly accurate when it was compared with exact solution.